2006
DOI: 10.1002/cphc.200600325
|View full text |Cite
|
Sign up to set email alerts
|

Hyperfine Coupling Tensors of the Benzosemiquinone Radical Anion from Car–Parrinello Molecular Dynamics

Abstract: Based on Car-Parrinello ab initio molecular dynamics simulations of the benzosemiquinone radical anion in both aqueous solution and the gas phase, density functional calculations provide the currently most refined EPR hyperfine coupling (HFC) tensors of semiquinone nuclei and solvent protons. For snapshots taken at regular intervals from the molecular dynamics trajectories, cluster models with different criteria for inclusion of water molecules and an additional continuum solvent model are used to analyse the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…However, it was demonstrated that the cusp problem can be overcome by adding very tight s functions to the Gaussian‐type basis sets . The verification of Gaussian‐type bases demonstrated that the double‐ζ sets are definitely too small for A iso calculations on isolated atoms, whereas they were successful in the case of polyatomic main‐group radicals including iminoxyls, nitroxides, and semiquinones . Surprisingly, inspection of Table shows that the isotropic HFCCs ( A iso ) due to the phosphorus nucleus in •PR 2 , when calculated at the DFT level, are rather sensitive to the size of the basis set.…”
Section: Resultsmentioning
confidence: 99%
“…However, it was demonstrated that the cusp problem can be overcome by adding very tight s functions to the Gaussian‐type basis sets . The verification of Gaussian‐type bases demonstrated that the double‐ζ sets are definitely too small for A iso calculations on isolated atoms, whereas they were successful in the case of polyatomic main‐group radicals including iminoxyls, nitroxides, and semiquinones . Surprisingly, inspection of Table shows that the isotropic HFCCs ( A iso ) due to the phosphorus nucleus in •PR 2 , when calculated at the DFT level, are rather sensitive to the size of the basis set.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of solvent effect on A F was compared to the reasons for EPR parameters changes reported for semiquinones [23][24][25][26][27][28][29][30][31] and nitroxides [32][33][34][35][36] . For these two types of radicals the solvent was shown to significantly alter their molecular and electronic structures, which brought about changes in the EPR parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of the HFC term is highly considerable, specifically for the phosphorus atoms, which active spin nuclei show a 100% natural abundance [24] and strongly affect the behavior of unpaired electrons in the PO(OR) 2 and 1 H atoms with the active nuclear spin is 99.985% 24 ) in water molecules and the ribose hydroxyls. In our computations the HFC for the named atoms includes the both isotropic and anisotropic terms; their analytical expressions might be found elsewhere [20][21][22]. The RP term includes the spin-spin electron coupling terms [22,23,[26][27][28] arising from the interaction between the AMP -, OH and hydrogens of water molecules and ribose hydroxyls.…”
Section: Geometry Parameters and Computationsmentioning
confidence: 99%
“…The gradient-corrected BLYP functional [30] is used with a plane-wave basis (cutoff: 70.0 Ry) and norm-conserving pseudopotentials of Troullier-Martins type [20][21][22]. The temperature of the simulation is set to 310 K. For the solvated system like ours the thermostatting is accomplished by rescaling the kinetic energy of the nuclei whenever the temperature is deviated more than a specific tolerance [30] (±10 K) from the desired 310 K temperature.…”
Section: Geometry Parameters and Computationsmentioning
confidence: 99%
See 1 more Smart Citation